Status of work alienation among nurses in China: A systematic review - You, Qian; Bai, Dingxi; Wu, Chenxi; Gao, Jing; Hou, Chaoming (Frontiers in Psychiatry, 2022)
Background Work alienation is a common feeling of estrangement from the work and its context. Nurses are prone to feel alienated due to the high risk of infection, heavy workload, and the persistence of stress at high level. Work alienation has serious negative outcomes, organizationally as well as personally. In recent years, the issue of work alienation among nurses has received considerable attention in China, but no systematic reviews have yet published and its epidemiological status among Chinese nurses remains unclear. Objective To systematically evaluate the status and distribution characteristics of work alienation among nurses in China. Methods CINAHL, Embase, Web of Science, PubMed, CENTRAL, Wanfang, SinoMed, CNKI, VIP were searched for cross-sectional studies before January 10, 2022 on the current status of work alienation among nurses. Two investigators independently screened the articles, extracted the data, and evaluated the risk of literature bias. Stata16.0 software was used for analysis. Results A total of 12 studies were included, with 7,265 nurses involved. Meta-analysis results showed that the score of work alienation was 35.43 [95%CI (31.82, 39.04)]. Subgroup analysis showed that the scores of male nurses and female nurses were 37.62 and 35.79; the scores of junior, undergraduate and graduate nurses were 34.90, 37.15, and 40.02; the scores of primary, intermediate, senior nurses were 36.95, 35.38, and 33.11; the scores of unmarried and married nurses were 38.59 and 36.70; the scores of nurses who had worked for 1~<6 years, 6~10 years, and more than 10 years were 37.46, 36.69, and 32.89; the scores of nurses with salary less than 5,000 yuan, 5,000~10,000 yuan, and more than 10,000 yuan were 40.25, 37.19 and 34.52; the scores of nurses in emergency department and intensive care unit, internal medicine, surgery, pediatrics were 37.25, 38.73, 36.28, and 31.98. Conclusion Chinese nurses had a moderate level of work alienation. The scores of men, high-educated, low- professional title, unmarried, shorter clinical working time, low-income, internal medicine, and emergency department and intensive care unit nurses were pretty high. Managers should take effective measures as soon as possible to reduce the occurrence of nurses’ sense of work alienation.